The Role of Trust in Shaping Purchase Decisions: Promotion, Design, and Insurance in Wuling Electric Vehicles - Andika, Sandy; Prastowo, Sugeng Lubar; Sutarjo, Sutarjo (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the influence of promotion and design on purchasing decisions for Wuling electric cars in Tangerang City, with consumer trust as a mediating variable and insurance as a moderating variable. A quantitative approach was employed using non-probability purposive sampling, involving 125 respondents. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results reveal that promotion has a significant positive effect on purchasing decisions, while design and consumer trust show no direct influence. Promotion, design, and insurance significantly affect consumer trust; however, insurance does not moderate the relationships between promotion, design, and consumer trust. Furthermore, consumer trust does not mediate the effects of promotion or design on purchasing decisions. These findings provide valuable implications for marketing strategies in the electric vehicle industry, particularly for Wuling, by emphasizing the importance of promotional effectiveness and the strategic management of factors shaping consumer trust.